Fretting-corrosion behavior in hip implant modular junctions: The influence of friction energy and pH variation. (September 2016) - Royhman, Dmitry; Patel, Megha; Runa, Maria J.; Wimmer, Markus A.; Jacobs, Joshua J.; Hallab, Nadim J.; Mathew, Mathew T.
Abstract: Background: Recently, there has been increasing concern in the orthopedic community over the use of hip implant modular devices due to an increasing number of reports of early failure, failure that has been attributed to fretting-corrosion at modular interfaces. Much is still unknown about the electrochemical and mechanical degradation mechanisms associated with the use of such devices. Purpose: Accordingly, the purpose of our study was to develop a methodology for testing the fretting-corrosion behavior of modular junctions. Methods: A fretting-corrosion apparatus was used to simulate the fretting-corrosion conditions of a CoCrMo hip implant head on a Ti6Al4V hip implant stem. The device features two perpendicularly-loaded CoCrMo pins that articulated against a Ti6Al4V rod. A sinusoidal fretting motion was applied to the rod at various displacement amplitudes (25, 50, 100, 150 and 200 μm) at a constant load of 200 N. Bovine calf serum at two different pH levels (3.0 and 7.6) was used to simulate the fluid environment around the joint. Experiments were conducted in two modes of electrochemical control – free-potential and potentiostatic. Electrochemical impedance spectroscopy tests were done before and after the fretting motion to assess changes in corrosion kinetics. Results: In free potential mode, differences were seen in change in potential as a function of displacement amplitude. In general, V Drop (the drop in potential at the onset of fretting), V Fretting, (the average potential during fretting), Δ V Fretting (the change in potential from the onset of fretting to its termination) and V Recovery (the change in potential from the termination of fretting until stabilization) appeared linear at both pH levels, but showed drastic deviation from linearity at 100 μm displacement amplitude. Subsequent EDS analysis revealed a large number of Ti deposits on the CoCrMo pin surfaces. Potentiostatic tests at both pH levels generally showed increasing current with increasing displacement amplitude. Electrochemical impedance spectroscopy measurements from free potential and potentiostatic tests indicated increased levels of resistance of the system after induction of the fretting motion. In free potential tests, the largest increase in impedance was found for the 100 μm group. Conclusions: We conclude that the 100 µm group exhibits deviations from linearity for several parameters, and this was most likely due to adhesive wear between Ti6Al4V and CoCrMo surfaces. Overall, the degradation of the system was dominated by wear at all pH levels, and displacement amplitudes.